2018
DOI: 10.1029/2018jd028880
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Rapid Drought Intensification Using the Climate Forecast System (CFS)

Abstract: In this study, a statistical method is developed to generate probabilistic forecasts of U.S. Drought Monitor (USDM)‐depicted drought intensification over two‐, four‐, and six‐week time periods using recent observations and forecast model output from the Climate Forecasting System (CFS). The predictors used include weekly anomalies in precipitation, potential evapotranspiration, dew point depression, and soil moisture computed over different time lags. A comparison between the baseline skill obtained using rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Instead, greater focus should be placed on predicting changes in soil moisture and vapor pressure deficit given their more dominant influence on ET. Indeed, a recent study by Lorenz et al (2018) has shown that inclusion of vapor pressure deficit and soil moisture predictions from climate models increased the accuracy of subseasonal drought intensification forecasts generated using a hybrid statistical method. This is also supported by a study by Seager et al (2015) that showed that large forest fires are often associated with very large vapor pressure deficits caused by antecedent surface drying and large-scale subsidence.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, greater focus should be placed on predicting changes in soil moisture and vapor pressure deficit given their more dominant influence on ET. Indeed, a recent study by Lorenz et al (2018) has shown that inclusion of vapor pressure deficit and soil moisture predictions from climate models increased the accuracy of subseasonal drought intensification forecasts generated using a hybrid statistical method. This is also supported by a study by Seager et al (2015) that showed that large forest fires are often associated with very large vapor pressure deficits caused by antecedent surface drying and large-scale subsidence.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Because ET estimates derived from infrared and visible satellite observations can only be computed when clouds do not obscure the surface, more complete domain coverage can be obtained by compositing clear-sky ET estimates over longer time periods (Anderson et al, 2013). Satellite-derived ET datasets covering regional and global domains can be obtained from a variety of sources, such as the MODIS Global Evapotranspiration Project (Mu et al, 2011), the Global Land Evaporation Amsterdam Model (Martens et al, 2017), and the Atmosphere-Land Exchange Inverse (ALEXI) model used to compute the Evaporative Stress Index (ESI) (Anderson et al, 2007a(Anderson et al, , b, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…• 15 described flash drought as a rapid onset or JoASC, Volume 2021, Issue 001 intensification drought event (Anderson et al 2011;Otkin et al 2014;Sun et al 2015;Brown et al 2016;Hobbins et al 2016Hobbins et al , 2017Cook et al 2018;Yao et al 2018;Otkin et al 2018a;Lorenz et al 2018;Gerkin et al 2018;Hoell et al 2019;Jin et al 2019;Trnka et al 2020). • Ten described flash drought as a short-term drought event (Senay et al 2008;Hunt et al 2014;Yuan et al 2015;Cammalleri et al 2016;Orbringer et al 2016;Sanchez et al 2016;Vogt et al 2018;Haile et al 2020;H.…”
Section: General Definitions or Descriptionsmentioning
confidence: 99%
“…Pendergrass et al (2020) proposed a two-category change in two weeks, while Chen et al (2019) also proposed a two-category change but over four weeks. Lorenz et al (2018), through some experimentation, considered "rapid onset" to mean any change toward drought within 2, 4, or 6 weeks. Ford et al (2015) looked for a three-category change toward drought in eight-weeks or less.…”
Section: The Us Drought Monitor In Flash Drought Definitionsmentioning
confidence: 99%
See 1 more Smart Citation